Analysis of Rocket Selection to Support the Fire Support Operations of the Marine Artillery Regiment's Rocket Battalion Using AHP and SWOT Methods - Arifin, Samsul; Tambunan, Darwin; Achmad, Achmad (AGUSPATI Research Institute, 2024)
The Marine Artillery Regiment is the operational command of the Marine Corps responsible for organizing the combat power of landing forces within the Marine Corps Artillery to support Amphibious Operations, Anti-Amphibious Operations, and Coastal Defense Operations on strategic islands. The purpose of Marine Artillery is to enhance the firepower of coastal defence task forces in order to thwart, destroy, or neutralize enemy Amphibious Operations and to prevent enemy troop and logistics transport ships from landing forces and their combat materials, as well as to anticipate the use of beaches and other facilities. For Fire Support Operations, the Marine Corps currently possesses the RM 70 Grad Rocket, RM 70 Vampire, and MLRS 90B Norinco. Therefore, research is needed to select the best rocket to support the Fire Support Operations of the Marine Artillery Regiment's Rocket Battalion. The methods used in this research are the Analytical Hierarchy Process (AHP) and Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis. The research results indicate that the MLRS 90B Norinco rocket is the best option for use in Marine Corps Fire Support Operations. Meanwhile, the best strategy to be employed is an aggressive strategy, which focuses on utilizing all strengths to seize and maximize opportunities.